Lymphadenectomy for early‐stage mucinous ovarian carcinoma. Issue 1 (January 2021) - Heyward, Quetrell D; Nasioudis, Dimitrios; Cory, Lori; Haggerty, Ashley F; Ko, Emily M; Latif, Nawar
Abstract : Objectives : There is evidence to suggest that the rate of lymph node metastases in patients with ovarian mucinous tumors is rare. The objective of this study was to investigate the prevalence of regional lymph node metastases among patients with apparent stage IA and IC mucinous ovarian carcinoma. Methods : A retrospective cohort study was performed and included patients from the National Cancer Database with apparent stage IA and IC mucinous ovarian tumors who underwent surgery between January 1, 2004 and December 31, 2015. Data collected included demographics, surgical procedures, and pathologic characteristics. The primary outcome was the effect of tumor stage, grade, and size on the risk of lymph node metastases. Categorical and continuous variables were compared using the χ 2 and Mann‐Whitney U tests, respectively. Results : A total of 4379 patients were identified: 3088 and 1213 with stage IA and IC disease, respectively, with an additional 78 patients who were stage I Not Otherwise Specified (NOS). Lymphadenectomy was performed in 70.6% of patients with stage IA and 70.3% of patients with stage IC cancers. Stratifying by grade, 68.4%, 71.3%, and 72.8% of patients with grades 1, 2, and 3 tumors underwent a lymphadenectomy, respectively. Furthermore, lymphadenectomy was performed in 64.9% of patients with tumors <10 cm and 72.4% with tumors >10 cm. Lymph node metastases were identified in 1.2% and 1.6% of patients with stage IA and IC disease, respectively (p=0.063). Additionally, metastases were present in 0.6% of patients with grade 1 tumors, 1.1% of patients with grade 2 tumors, and 5.3% of patients with grade 3 tumors (p<0.001). Lastly, 0.9% of patients with tumors <10 cm and 1.4% of patients with tumors >10 cm had lymph node metastases (p=0.19). Conclusions : Among patients with mucinous ovarian carcinoma, lymph node metastases are rare. However, metastases are significantly more common in patients with higher grade tumors. These factors may be considered when making decisions regarding the need for lymphadenectomy in early‐stage mucinous ovarian tumors.